2016
DOI: 10.3390/molecules21101389
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Secondary Metabolites from Plants as Drugs or Leads against Protozoan Neglected Diseases—Part III: In-Silico Molecular Docking Investigations

Abstract: Malaria, leishmaniasis, Chagas disease, and human African trypanosomiasis continue to cause considerable suffering and death in developing countries. Current treatment options for these parasitic protozoal diseases generally have severe side effects, may be ineffective or unavailable, and resistance is emerging. There is a constant need to discover new chemotherapeutic agents for these parasitic infections, and natural products continue to serve as a potential source. This review presents molecular docking stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 417 publications
(257 reference statements)
0
24
0
Order By: Relevance
“…Considering the chemical diversity observed among algal metabolites that were active against the etiological agents of NDs as their model microorganisms and the fewer studies approaching their mechanisms of action, it is not possible to suggest features of structure-bioactivity. Ogungbe and Setzer (2016) reviewed molecular targets for Leishmania, Trypanosoma, and Plasmodium spp. parasites and showed that several classes of phytochemicals, including geranylgeraniol, steroids, and phenols, presented an antioxidant enzyme, trypanothione reductase, as their target.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the chemical diversity observed among algal metabolites that were active against the etiological agents of NDs as their model microorganisms and the fewer studies approaching their mechanisms of action, it is not possible to suggest features of structure-bioactivity. Ogungbe and Setzer (2016) reviewed molecular targets for Leishmania, Trypanosoma, and Plasmodium spp. parasites and showed that several classes of phytochemicals, including geranylgeraniol, steroids, and phenols, presented an antioxidant enzyme, trypanothione reductase, as their target.…”
Section: Discussionmentioning
confidence: 99%
“…Both components have been the subject of intensive research and development in both academic and commercial settings. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Nonetheless, computational methods for pose prediction and affinity ranking have yet to fulfill their perceived promise, as neither is yet fully reliable. [45][46][47][48][49][50][51] In fact, it is surprisingly difficult even to compare the reliability of various methods in a consistent manner, and this limitation makes it correspondingly difficult to make and verify technical progress.…”
Section: Introductionmentioning
confidence: 99%
“…Despite much research and development, there is no approved vaccine for S. aureus. In view of this situation researchers are searching new antimicrobial substances that are natural plant-based economically feasible which are expected to be good sources of novel phytomedicine and an effective alternative antimicrobial, anticancer, anti-inflammatory, anti-diabetic and other chemotherapeutic agents [27,28].…”
Section: Introductionmentioning
confidence: 99%